KONTRIBUSI KONSEP DIRI TERHADAP MOTIVASI BERPRESTASI SISWA DI SMP NEGERI BATANG KAPAS (Universitas PGRI Sumatera Barat, 2015)
phenomenon of the students’ low motivation to get the achievement at school. Self concept have a correlation for creating the students’ potential giftedness to get an achievement in learning. The role of the teachers in improving the students’ achievement at school in order to improve their learning achievement. This research has purpose to find the self concept and achievement motivation of SMPN Batang Kapas. This research used correlational approach which has purpose to know how is the contribution among the research variables. The population of the research is the students of SMPN Batang Kapas. The amount of the population was 601 students. The sample of this research was 240 students. It had been taken by using simple random sampling technique. The instruments used in the form of scale. The data was analyzed by using descriptive technique and the hypothesis testing was done by using simple regression analysis . The result shows that: (1) the self concept is in the enough category, (2) students’ achievement motivation is in the enough category, (3) the contribution of self concept through the students’ achievement motivation is about 14.4%. The results imply that self concept are factors that have contributed to students achievement motivation, but there are many other factors that influence students achievement motivation.